HUBUNGAN KELINCAHAN DENGAN KETERAMPILAN PASSING BAWAH ATLET BOLAVOLI MINI DI SDN 34 PENEBAL KECAMATAN BENGKALIS - Agusrizal Agusrizal; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, research problem is the passing down skills of students in the game of volleyball is not so good, as expected. Many factors lead to low down the passing skills include agility factor owned by the students. The purpose of this study was to determine the relationship agility with passing skills down mini volleyball athletes in SDN 34 Thickening District of Bengkalis. This type of research is correlational, the population is all students who participated in the training mini volleyball at SDN 34 Thickening District of Bengkalis, numbering as many as 20 people. The sample in this study were taken using total sampling technique. Thus the number of samples in this study amounted to as much as 20orang. The type of data in the study of primary data, data obtained directly from the respondents to test agility and passing skills tests below. While secondary data is data about the number of students who obtained from the Administrative Office of the school concerned. Data dinalasis by using product moment. Based on the analysis of data obtained rhitung 0.574> 0.444 rtabel means there is a significant correlation (meaning) between agility with passing skills down mini volleyball athletes in state elementary school SDN 34 Thickening District of Bengkalis, accepted the truth empirically.Keywords : Agility, passing skills down